More than Mere Ornaments: Female Visitors to Sir Richard Wallace’s Art Collection - Helen C. Jones (19, 2021)
The Visitors’ Book kept by Sir Richard and Lady Wallace at Hertford House encompasses 245 pages within its black leather covers and includes a treasure trove of nineteenth-century signatures, most of which have now been transcribed during a year-long project. Many of the signatories have been identified, and this research, which has unearthed intriguing stories about some of the female visitors to the collection, forms the basis for this article. Several of these women visitors to Hertford House turn out to have had fascinating lives, being active in fields such as medicine, archaeology, and women’s rights. The achievements of twenty-four of them, grouped into nine loose, and sometimes surprising, categories are examined in this article. Their connections to the world of art and the ways in which they were able to take part in public life have also been charted. Most of the women defied general expectations of a woman’s life in the nineteenth century. They were able to attain an excellent education, were supported in their unusual ambitions by their families, and, if married, lived reasonably independent lives. However, their struggles to attain their goals were real and should not be underestimated. The women described here were more fortunate than others of their time but nevertheless had to make the most of every opportunity within their grasp in order to succeed. This research has, moreover, confirmed the value of studying visitors’ books as a route to examining lives in the past.